Google Earth® Models with COLLADA and WxAzygy® Transparent Interface: An example from Grotto Creek, Front Ranges, Canadian Cordillera - Boggs, Katherine J.E.; Dordevic, Mladen M.; Shipley, Scott T. (Geoscience Canada, 2012)
Virtual globes represent a paradigm shift for geoscience education. It is now possible to explore real world experiences across the entire Earth, the Moon, and Mars, and also to combine multiple 2-D images into one 3-D image with topography. Models viewed in Google Earth® are more intuitive for visualizing 3-D geological structures than traditional paper maps and cross-sections. Here a student-constructed geological map and cross-sections from an introductory field school are used to illustrate the creation of a draped geological map over topography. A custom vertical slider elevates the cross-sections above topography and a horizontal slider restores thrust faulting. Models located in situ in topography are made queryable via a ‘cut-away’ using the WxAzygy® transparent interface. SOMMAIRE La notion de « globes virtuels » constitue un changement de paradigme dans le domaine de l’éducation en géoscience. Il est maintenant possible de traiter de la réalité de tous les recoins de la Terre, de la lune et de Mars, et aussi de combiner de multiples images 2-D en une image 3-D affichant la topographie. Les modèles de Google Earth® permettent une visualisation 3-D plus intuitive des structures géologiques que ne le permettent les cartes papiers usuelles et les coupes. Dans la présente, une carte géologique et une coupe réalisées par un étudiant d’un cours d’introduction au travail de terrain sont utilisées pour illustrer la confection d’une carte géologique appliquée sur la topographie correspondante. Un curseur vertical personnalisé dessine les coupes au-dessus de la topographie, et un curseur horizontal permet de restaurer les failles de chevauchement. Ces modèles ancrés au droit de la topographie peuvent être exploiter au moyen d’un écorché produit par l’interface transparent WxAzygy®.